Existence of multiple solutions for a perturbed discrete anisotropic equation. Issue 9 (2nd September 2017) - Heidarkhani, Shapour; Afrouzi, Ghasem A.; Moradi, Shahin; Caristi, Giuseppe
Abstract: In this paper, we are concerned with the existence of at least three distinct solutions for a perturbed anisotropic discrete Dirichlet problem. The approach is based on variational methods. We also provide two examples in order to illustrate the results.